a Comparative analysis of the performance of Islamic and conventional banks: does corporate governance matter? - Aslam, Ejaz; Haron, Razali; Ahmad, Salman (Inderscience, 2019)
The purpose of this study is to investigate the impact of corporate governance (CG) internal structure on the performance of Islamic and conventional banking system in Pakistan. To account for the problem of heteroscedasticity, this study used GLS estimation technique by using a sample of five fully fledged Islamic and 15 conventional banks for the period from 2006 to 2015. The study finds that board size and its composition largely contribute to the Islamic and conventional banking performance. However, board committees have an insignificant relationship with the performance of conventional and Islamic banks that demands further investigation into the structure and powers of the board committees. In short, this study provides evidence that corporate governance does matter for the performance of Islamic and conventional banking. The current findings are useful for the policymakers and regulators to improve the existing governance structure for achieving better performance in the financial sector.